ON THE SOLUTIONS OF COUPLED SYSTEMS OF DELAY DIFFERENTIAL EQUATIONS (Comprehensive Journal of Science, 2025)
This paper studies the qualitative behavior of solutions to coupled systems of delay differential equations. Sufficient conditions for the existence and uniqueness of solutions are established using fixed point techniques in appropriate Banach spaces. examines the effect of coupling and time-delay parameters on the stability properties of the system. The results contribute to a deeper theoretical understanding of coupled delay differential systems and support their applicability in various mathematical and applied modeling contexts.
Keywords: Coupled system, Delay differential equation, Fixed point theorem